PENGARUH LINGKUNGAN SOSIAL TERHADAP SELF EFFICACY PADA ANAK REMAJA : lingkungan sosial terhadap self efficacy - suriani; Alhuda; Dedy Ahmady; Roslaini (Sekolah Tinggi Ilmu Kesehatan Muhammadiyah Lhokseumawe, 2022)
The social environment is one that influences a person to take action and changes for each individual. Self-efficacy continues to develop and can change with increasing age, increasing experience and expanding the social environment. Children begin to learn from the environment and their friends at play. The process of forming self-efficacy at school age is cognitively formed and developing. The general objective is to identify the influence of the social environment on self-efficacy in adolescents at SMP N 7 Baktiya, kabupaten Aceh Utara. This type of research is analytic, the design used is a cross-sectional study. Total population is 59 students of SMP N 7 Baktiya, Kabupaten Aceh Utara. The sample used is total sampling. The results obtained p-value 0.051 by doing the Chi-square test. There is no relationship between the influence of the social environment on self-efficacy in adolescents at SMP N 7 Baktiya Kabupaten Aceh Utara. Researcher's suggestions increase knowledge about the influence of the social environment, school environment and self-efficacy on adolescents. Increase the number of variables studied, increase the number of samples for the sake of enriching scientific knowledge and so on.